Geronimo Stilton Cavemice #5: The Great Mouse Race - Hopewell, Sarah (Scholastic Paperbacks, 2014)
Geronimo Stilton's ancient ancestor Geronimo Stiltonoot is back in another prehistoric adventure! It's the season for the annual cavemouse sports competition! This year, Tiger Khan and his saber-toothed henchmen want to enter the games. They call a truce with the cavemice during the tournament . . . but when their flag goes missing, Tiger Khan is furious. Can Geronimo Stiltonoot track it down in time to keep his fur intact?